2017
DOI: 10.1101/231373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring mosquito-borne viral suitability in Myanmar and implications for local Zika virus transmission

Abstract: 19In South East Asia, mosquito-borne viruses have long been recognised as a cause of high disease 20 burden and significant economic costs. While certain countries in the region often serve as robust 21 references for epidemiological data on particular mosquito-borne viruses, our current understanding of

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…On the other hand, low elevations or sea level (coastal areas) maintain a high correlation with the Zika presence of cases (r=-0.454 p <0.000) such findings are consistent with other studies. 12,17,18 Previous studies have shown that density population is an important factor in the transmission of ETV's such as Zika, which is consistent with the moderate correlation observed (r=0.311 p<0.005) which indicates that Zika cases are correlated with high population densities where there is supposed to be a greater Zika transmission of cases. 12,19,20 The variables identified by this study directly affect the vector biology and therefore the occurrence of outbreaks, so it is very important to conduct more research where entomological information.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, low elevations or sea level (coastal areas) maintain a high correlation with the Zika presence of cases (r=-0.454 p <0.000) such findings are consistent with other studies. 12,17,18 Previous studies have shown that density population is an important factor in the transmission of ETV's such as Zika, which is consistent with the moderate correlation observed (r=0.311 p<0.005) which indicates that Zika cases are correlated with high population densities where there is supposed to be a greater Zika transmission of cases. 12,19,20 The variables identified by this study directly affect the vector biology and therefore the occurrence of outbreaks, so it is very important to conduct more research where entomological information.…”
Section: Discussionsupporting
confidence: 80%